Optimalisasi Potensi Desa Wisata Sibetan Melalui Pelatihan Terpadu bagi Perangkat Desa dan Pemandu Wisata - I Made, Widiantara; Muderana, I Ketut; Teristiyani Winaya, Nyoman (J-Dinamika : Jurnal Pengabdian Masyarakat, 2025)
Sibetan Village in Bebandem District, Karangasem Regency has great potential as a tourist village with an agrotourism area of 8,326 hectares. However, the development of this potential is constrained by three issues: a suboptimal archive management system, limited social media content creation capabilities, and low English language proficiency among tour guides. This community service program was implemented to address these constraints through integrated training involving 25 village officials and 35 tour guides. The training was conducted in parallel at two different locations: Sibetan Village Office for archive management training and Banjar Mantri Hall for social media and English language training. The training method combined lecture delivery, demonstration, and hands-on practice. The program resulted in three significant changes: a more structured archive management system, strengthened digital promotion through social media, and improved English language skills among tour guides. Evaluation results showed high participant satisfaction, with 52.4% being very satisfied and 47.6% satisfied with the program implementation. The program's impact was also evident from 100% of participants stating the program improved their productivity, while 85% requested the program to be conducted regularly every 6 months. This community service program has successfully laid a strong foundation for developing Sibetan Village as a sustainable tourist destination through human resource capacity building.